EFFECT OF CARBON BLACK/SILICA HYBRID REINFORCEMENT ON THE PROPERTIES OF SOLID TIRE TREAD COMPOUND CONTAINING GROUND TIRE RUBBER - Umunakwe, Ifeoma Janefrances; Malomo, Dosu; Umunakwe, Reginald (FUDMA Journal of Sciences, 2023)
The incorporation of ground tire rubber (GTR) in rubber compounds results to reduced strength of the rubber vulcanizates. The need to improve the properties of rubber vulcanizates containing GTR becomes necessary. This work evaluates the effect of hybrid filler reinforcement on the abrasion resistance, hardness, heat build-up, dynamic set and compression set of solid tire tread compound containing 10 phr and 20 phr of 60 mesh size GTR. The hybrid filler used was carbon black/silica (CB/SiO2) in the ratio 60/0, 55/5, 50/10 and 45/15 phr respectively. The mixing followed two step mixing method and standard samples for testing were molded through compression molding technique at 150, under the pressure of 20 tons force and cure time based on the optimal cure time from rheometric measurement. Results show that abrasion volume loss was reduced with GTR addition while the samples containing hybrid filler showed slightly higher abrasion loss that than those containing GTR and filled with only carbon black. At 10 phr GTR loading, the desired reduction in the hardness of the vulcanizates containing GTR was achieved through the use of hybrid filler reinforcement; only small reduction was achieved at 20 phr GTR loading. At the optimal hybrid CB/SiO2 reinforcement ratio (50/10), the properties of the solid tire tread vulcanizates were better than those of the samples filled with 55/5 and 45/15 hybrid CB/SiO2 reinforcement. It is recommended that the use of hybrid CB/SiO2 hybrid reinforcement at the optimal silica content be explored by tire industries exploring the incorporation GTR in...